Utilization of Plants in Fatusene Village Water Sources for the North Central Timor Region Water Conservation: Pemanfaatan Tumbuhan di Beberapa Sumber Mata Air Desa Fatusene Untuk Konservasi Mata Air Wilayah Timor Tengah Utara - Remigius Binsasi; Willem Amu Blegur; Polikarpia Wilhelmina Bani; Yolanda G. Naisumu (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
The presence of plants plays an important role in the availability of water in springs. Plants maintain water balance, even water distribution patterns, and the preservation of water resources, both in quality and quantity. This activity is carried out to develop a strategy for preserving plants around springs. The activity is carried out using the method of socialization, planting species, installing labels on each species, installing notice boards at each spring as an appeal and testing water quality. The results of the activity show that water conservation can be carried out by identifying plants of the water consumed and water conservor types, plants are cultivated and preserved for water conservation, naming species that have conservation value and making positive and persuasive appeals. These appeals can increase public understanding and perception which has an impact on behavior and actions for vegetation and water conservation. Factors that influence the process of plant utilization include the influence of rainfall, soil conditions, the presence of water sources, proximity to residence, and water quality. The strategy for preserving plants around springs can be carried out by conserving plants around springs. Water quality testing needs to be carried out periodically to maintain water quality.